ផលប ៉ះពាល់ពីការសាងសង់ទំនប់ទៅទលីជលផលទៅក្នុងទទនេទេគងគ - Geheb, Kim; Pukinskis, Ilse (CGIAR Challenge Program on Water and Food, 2012)
Reviews current literature on impacts of dams on fisheries, including: fishery basics, fish migrations, habitats, biodiversity, aguaculture production and reservoir fisheries.